Efficient and selective removal of radioactive iodine anions using engineered nanocomposite membranes. Issue 11 (15th September 2017) - Mushtaq, Sajid; Yun, Seong-Jae; Yang, Jung Eun; Jeong, Sun-Wook; Shim, Ha Eun; Choi, Mi Hee; Park, Sang Hyun; Choi, Yong Jun; Jeon, Jongho
Abstract : A hybrid membrane consisting of gold nanoparticles immobilized on cellulose acetate has been developed for the selective removal of radioactive iodine from various aqueous media. Abstract : The efficient treatment of radioactive waste arising from nuclear accidents and overuse of radioisotopes has become an important issue, and much effort has been devoted to protecting the environment from such toxic radioactive materials. Among them, radioactive iodine in water is regarded as one of the most palpable threats to humans, as it is generated by post-use in medical and industrial applications. Although a few adsorbents and purification processes have been reported, the development of a better desalination method that is able to provide high removal efficiency, ion-selectivity, and reusability is still in demand. Herein, we report a hybrid composite membrane, composed of gold nanoparticles and cellulose acetate membranes, which has the potential to be used for efficient desalination of radioactive iodine. A single filtration process using this membrane provided high removal efficiency with more than two orders of magnitude iodide anion removal within a minute and excellent ion-selectivity. Moreover, the same operation can be applied several times without significant decrease of its performance. Therefore, it is anticipated that our work will be a new avenue for desalination of radioactive iodine in various aqueous media.